BATIK TRAINING FOR THE COLLABORATION OF FILIPINA MOTIF BATIK AND INDONESIAN MOTIFS (JAVANESE MOTIF) - Setiawan, Ari; Darmayani , Satya; As’ad, Ihwana; Diawati, Prety; Widiastuti, Ima; Gabriel W. Aguilar, Mark; Syamsi, Nur (SMARTINDO, 2025)
The purpose of this community service is to introduce various batik motifs in Jogja and in the Philippines, increase understanding related to batik marketing and establish cooperation in strengthening batik motifs and their promotion on both sides. This community service was carried out in three stages: 1. Focus Group Discussion Stage Collecting data related to batik motifs and discussions related to batik activities in batik villages with resource persons from Indonesia and the Philippines. By using the FGD method and the Sharing Section method, it is hoped that the village can be more comfortable in communicating with the service team.2. Socialization Stage The socialization method was chosen to present the solutions that had been carried out in the previous stage. Socialization is carried out offline using an approach by directly interacting actively with the batik makers while conveying the material discussed in the socialization in the form of: a) Various kinds of Indonesian batik motifs, especially Javanese batik motifs and also Philippine batik motifs.b) How to make batik and introduce batik motifs.3. Action Stage and In the action stage, the service team uses the mentoring method or mentoring method.The results and conclusions of this community service are: 1. The service was successfully carried out well, this is evidenced by the enthusiasm of the participants who participated in the activities during the service by paying attention to every material provided both related to batik motifs and batik marketing. 2. Participants gave a very good response as evidenced by the many questions and discussions during the service, besides that the participants expressed their satisfaction in participating in this activity through the responses given when the service was completed.3. Participants also expressed their gratitude to the servants from both the Philippines and Indonesia because of the increased knowledge gained, especially batik motifs and batik marketing abroad.